2017
DOI: 10.13005/ojc/330252
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Flavonoids in Iraqi Date Palm Pollen by HPLC

Abstract: Date palm pollen-DPP (Phoenix dactylifera L) plays an important role in traditional treatment in Iraq, especially for the treatment of fertility or as supplements, flavonoids were important components for date palm pollen, no information is available in the literature about the types of flavonoids in an Iraqi DPP variety El-Ghannmi Ahmar. The HPLC analysis revealed that in an Iraqi DPP variety El-Ghannmi Ahmar contains many types of flavonoids (13.590 µg/g lincoceric acid, 122.251 µg/ gIsorhamnetin,71.146 µg/g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 6 publications
(6 reference statements)
0
5
0
Order By: Relevance
“…Other flavonoid aglycones were quantified in very low amounts such as luteolin, apigenin, and naringenin. The results obtained in the work of Al-Samarrai et al indicated that date palm pollen has some level of naringin (64.574 mg/kg), and apigenin (109.117 mg/kg) too [60].…”
Section: Resultsmentioning
confidence: 99%
“…Other flavonoid aglycones were quantified in very low amounts such as luteolin, apigenin, and naringenin. The results obtained in the work of Al-Samarrai et al indicated that date palm pollen has some level of naringin (64.574 mg/kg), and apigenin (109.117 mg/kg) too [60].…”
Section: Resultsmentioning
confidence: 99%
“…apigenin, luteolin, isorhamnetin, apigenin-7-O-β-glucuronide, luteolin-7-O-glucuronide and naringin) and phytosterols ( i.e. stigmasterol) 28 , 29 ( Fig. 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…As mentioned in above sections, studies reported that DPP comprised different classes of natural products including non-flavonoids (especially phenolic acids), flavonoids, 29 amino acids including aspartic, proline, threonine, phenylalanine, alanine, glycine, arginine, methionine, isoleucine, leucine, tyrosine, glutamine, lysine, histidine, valine, and serine, 69 vitamins (B1, B2, B12, A, D, C, E), 68 fatty acids, phytosterols, 68 and mineral and trace elements (e.g. potassium, calcium, sodium, manganese, phosphorous, zinc, iron, selenium).…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Moreover, Daoud et al, (2015) found that the pollen of Tunisian date palm cultivars contain high concentrations of flavonoids, and four types of flavonoids which include quercitin, rutin, catechin and epicatechin. Recently, AL-Samarrai et al, (2017) found that Iraqi pollen date palm contain many types of flavonoids (lincoceric acid, chlorogenic acid, ferulic acid, naringin, apigenin-7-O-beta glycopyranoside, letulin and letulin-7-O-beta glycosides).…”
Section: Table1 General Pollen Features Of the Examined Phoenix Dactylifera Cultivarsmentioning
confidence: 99%